Fabrication and Characterisation of Stimuli Responsive Piezoelectric PVDF and Hydroxyapatite-Filled PVDF Fibrous Membranes - Biranche Tandon; Prashant Kamble; Richard T. Olsson; Jonny J. Blaker; Sarah H. Cartmell (Molecules, 2019)
Poly(vinylidene fluoride) has attracted interest from the biomaterials community owing to its stimuli responsive piezoelectric property and promising results for application in the field of tissue engineering. Here, solution blow spinning and electrospinning were employed to fabricate PVDF fibres and the variation in resultant fibre properties assessed. The proportion of piezoelectric β-phase in the solution blow spun fibres was higher than electrospun fibres. Fibre production rate was circa three times higher for solution blow spinning compared to electrospinning for the conditions explored. However, the solution blow spinning method resulted in higher fibre variability between fabricated batches. Fibrous membranes are capable of generating different cellular response depending on fibre diameter. For this reason, electrospun fibres with micron and sub-micron diameters were fabricated, along with successful inclusion of hydroxyapatite particles to fabricate stimuli responsive bioactive fibres.